A 60–50 ka African Humid Period modulated by stadial Heinrich events HE6 and HE5a in northwestern Africa - (:unkn) unknown (My University, 2024)
A Late Pleistocene lacustrine sedimentary succession has recently been discovered and investigated in Northwest Africa (Morocco, Anti-Atlas, Agadir-Tissint Feija). By integrating new radiometric 230Th/U and OSL ages and new clay mineral analyses with previous sedimentological evidence, we significantly refine the origin and the timing of this succession and its significance for African paleoenvironments and paleoclimate. The sedimentary succession reflects the evolution of a paleolake, referred to as paleolake Tissint, that indicates the abrupt establishment of a wet period at ~60 ka and a gradual return to drier conditions at ~50 ka. Establishment of this paleolake coincides with a peak of precession-forced high summer insolation centered around ~60 ka suggesting that orbital parameters triggered humid conditions in northwest Africa during this time interval. Comparing this observation with others from the literature, it appears that continental-scale wet conditions prevailed across North, Central and East Africa at that time and add evidence in support of a 60–50 ka African Humid Period (AHP). Given that the Holocene African Humid Period was associated with “Green Sahara” conditions, wet conditions between 60 and 50 ka likely sustained coeval greening, at least partially, of the Sahara region. In northwest Africa, the 60–50 ka AHP is affected by Heinrich Event HE6 which via adjustment of the Atlantic Meridional Ocean Circulation (AMOC) seems to have delayed the onset of this AHP. In a similar way, the younger Heinrich Event 5a resulted in short-term regional aridification about 55 ka ago that briefly interrupted the generally wetter period. Finally, as the AHP between ~60 ka and ~ 50 ka coincides with a major Human dispersal out of Africa; these particular conditions may have offered a climatic window of opportunity for Homo sapiens to open migration routes across Africa towards the Levant.
Keywords: African Research